Connection of extruded subnets a solution based on RSIP. - De Launois, C. (IEEE Communications magazine)
Extruded subnets is the name given to a new type of subnetworks, connected to the Internet through "wideband" residential access lines, such as asynchronous digital subscriber line (ADSL) or cable connections, but seamlessly integrated into their remote corporate network. Extruded subnets are designed to completely hide the fact that they are remote. This article presents the constraints and requirements of extruded networks, and discusses the problems and solutions of their implementation. A new solution is proposed. It is based on IPSec and Realm Specific IP protocol (RSIP), a protocol published as an RFC, mainly as an alternative to Network Address Translating (NAT). An extension is proposed to RSIP in order to improve the scalability of the solution. The use of IPSEC and the extended RSIP satisfies all the requirements for extruded subnets and enjoys excellent scalability. This extruded subnet implementation is now available as open source software